The smart building advantage : unlocking the value of smart building technologies - Marson, Matthew (Emerald Publishing Limited, 2024)
The Smart Building Advantage introduces and explores the fascinating world of cutting-edge technology, sustainable design, and the incredible potential of smart buildings. This book is a roadmap to understanding the transformative power of smart building technologies and how they can deliver an astonishing return on investment for those who can harness their power. The world of real estate and building management is rapidly evolving, with the adoption of smart technologies becoming increasingly essential. The concept of a "smart building" goes far beyond mere convenience; it's a strategic investment that promises substantial financial gains and environmental benefits. From reducing energy consumption and optimising space usage to enhancing occupant comfort and reducing productivity leakage, the benefits of smart buildings are far-reaching and compelling. Drawing on a wealth of real-world experiences, global reach, and practical guidance, this book: demystifies the complex landscape of smart building implementation and the business cases that make them a reality; provides a comprehensive framework for decision-makers, property owners, designers, and facility managers and more to leverage the power of smart technologies effectively; discovers how smart buildings not only contribute to sustainability goals but also enhance property values and tenant satisfaction; offers an in-depth exploration of how the integration of sensors, data analytics, and automation can lead to a remarkable return on investment. Presenting compelling evidence and actionable strategies, The Smart Building Advantage is a must-read for anyone interested in the intersection of emerging technology, sustainability, and the built environment. Whether you are a seasoned industry professional or a newcomer eager to unlock the potential of smart buildings, this book will equip you with the knowledge and tools to embark on a transformative journey toward smarter, more efficient, and more profitable buildings.
Includes index.
Keywords: Sustainable buildings -- Design and construction.; Architecture -- Technological innovations.; Technology & Engineering -- Construction -- General.; Structural engineering.; Building construction and materials.; Building skills and trades.; elektronické knihy; electronic books